Future Projections of Water Scarcity in the Danube River Basin Due to Land Use, Water Demand and Climate Change - Bisselink, Berny; de Roo, Ad; Bernhard, Jeroen; Gelati, Emiliano (Journal of Environmental Geography, 2018)
This paper presents a state-of-the-art integrated model assessment to estimate the impacts of the 2°C global mean temperature increase and the 2061-2090 warming period on water scarcity in the Danube River Basin under the RCP8.5 scenario. The Water Exploitation Index Plus (WEI+) is used to calculate changes in both spatial extent and people exposed to water scarcity due to land use, water demand, population and climate change. Despite model and data uncertainties, the combined effects of projected land use, water demand and climate change show a decrease in the number of people exposed to water scarcity during the 2°C warming period and an increase in the 2061-2090 period in the Danube River Basin. However, the projected population change results in a decrease of exposed people in both warming periods. Regions with population growth, in the northwestern part of the Danube River Basin experience low water scarcity or a decrease in water scarcity. The largest number of people vulnerable to water scarcity within the Danube River Basin are living in the Great Morava, Bulgarian Danube and Romanian Danube. There, the combined effects of land use, water demand and climate change exacerbate already existing water scarce areas during the 2°C warming period and towards the end of the century new water scarce areas are created. Although less critical during the 2°C warming period, adjacent regions such as the Tisza, Middle Danube and Siret-Prut are susceptible to experience similar exposure to water scarcity within the 2061-2090 period. Climate change is the most important driver for the increase in water scarcity in these regions, but the strengthening effect of water demand (energy sector) and dampening effect of land use change (urbanization) does play a role as well. Therefore, while preparing for times of increased pressures on the water supply it would be advisable for several economic sectors to explore and implement water efficiency measures.